The epistemology of democracy: The epistemic virtues of democracy - Prijić-Samaržija Snježana (Filozofija i Društvo, 2020)
The new and vibrant field of the epistemology of democracy, or the inquiry about the epistemic justification of democracy as a social system of procedures, institutions, and practices, as a cross-disciplinary endeavour, necessarily encounters both epistemologists and political philosophers. Despite possible complaints that this kind of discussion is either insufficiently epistemological or insufficiently political, my approach explicitly aims to harmonize the political and epistemic justification of democracy. In this article, I tackle some fundamental issues concerning the nature of the epistemic justification of democracy and the best theoretical framework for harmonizing political and epistemic values. I also inquire whether the proposed division of epistemic labour and the inclusion of experts can indeed improve the epistemic quality of decision-making without jeopardizing political justification. More specifically, I argue in favour of three theses. First, not only democratic procedures but also the outcomes of democracy, as a social system, need to be epistemically virtuous. Second, democracy’s epistemic virtues are more than just a tool for achieving political goals. Third, an appropriate division of epistemic labour has to overcome the limitations of both individual and collective intelligence.